Element localization in archaeological bone using synchrotron radiation X-ray fluorescence: identification of biogenic uptake - Swanston, Treena; Varney, Tamara L.; Coulthard, Ian; Feng, Renfei; Bewer, Brian; Murphy, Reg; Hennig, Cheryl; Cooper, David M. L. (My University, 2012)
Trace element analysis related to archaeological bone is viewed as one way to determine levels of element exposure in past populations. This area of research is complex because there is the potential for the incorporation of trace elements from the burial environment into archaeological bone. We tested the hypothesis that matching the spatial distribution of trace elements within cortical bone with the biological structures would provide evidence of biogenic uptake. We examined samples from a non-segregated Royal British Naval cemetery (1793–1822) in Antigua, West Indies. A key historical question related to this population was the extent of exposure to lead and the resulting health effects. Images from conventional light microscopy (histological) analysis of the bone samples were matched with elemental maps of calcium, strontium, and lead that were created through the use of synchrotron radiation X-ray fluorescence (SR-XRF). Biogenic uptake of both strontium and lead was indicated based on the localization of these trace elements within discreet microstructural elements. The successful integration of histological information with XRF data is a powerful technique for the interpretation of past biological events through trace elements.
Keywords: bone; SR-XRF; microarchitecture; strontium; lead